Response of Safflower (Carthamus tinctorius L.) to Planting Rate and Row Spacing in a High Altitude Enviroment - SEFAOĞLU, Fırat; ÖZER, Hakan (Erciyes Universitesi, 2022)
Safflower (Carthamus tinctorius L.), has the potential to be an important oilseed crop in Eastern Anatolia, Turkey. In this region with a semi-arid climate, there is no scientific study about row spacing and planting rate in safflower. Therefore, this study was conducted to investigate the effects of row spacing and planting rate on yield and agronomic properties of safflower cultivars (Dinçer and Yenice) in dry conditions, in the years 2013 and 2014. Three different row spacings (20, 40 and 60 cm) and planting rates (20, 40 and 60 kg ha-1) were tested. In both study years, it was determined that seeding rate, row spacing and cultivars have significant effects on plant growth, yield and yield components. The cultivars responded similarly to both treatments that row spacing and planting norm in terms of seed yield in both research years. It was determined that the examined plant characters were significantly affected by the treatments, and the oil concentration, seed, and oil yield increased with increased row spacing and planting rate. The results obtained from this study emphasize the importance of the choice of suitable row spacing and planting rate in safflower production in semi-arid environments and the seed yield in safflower could be increased by narrow plantings (i.e.the 20 and 40 cm row spacings with 60 kg ha-1planting rate.
Keywords: Carthamus tinctorius; planting rate; row sapacing; Safflower; seed yield; Ziraat Mühendisliği; Agricultural Engineering; Carthamus tinctorius; planting rate; row sapacing; safflower; seed yiield; 2. Zero hunger; 15. Life on land